Evaluasi penerapan pengendalian intern sistem informasi akuntansi penggajian karyawan outsourcing pada PT Berkat Usaha Anak Sejahtera - Dinda Yolania Novela; Fitriana Santi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
This study aims to determine how the application of internal recognition of the payroll accounting information system of outsourcing employees at PT Berkat Usaha Anak Sejahtera. The object of this research is PT Berkat Usaha Anak Sejahtera. This research method uses a qualitative descriptive method by conducting direct interviews with the director, secretary, and field supervisor of PT Berkat Usaha Anak Sejahtera. The data sources of this research are primary data obtained from interviews, observations, and field research. From the results of the research that has been done, it can be concluded that there is a weakness in the payroll accounting information system for outsourcing employees, namely the company does not make or set a payroll SOP (Standard Operating Procedure). There are also weaknesses in the implementation of internal control of the payroll accounting information system where the company does not update the organizational structure, moreover there are dual responsibilities and functions carried out by the director.